A Planar Broadband Circularly Polarized Antenna with End-Fire Radiation. Issue 4 (19th May 2017) - Mo, Wendong; Zhang, Wenmei; Yang, Rongcao; Zeng, Qingsheng
ABSTRACT: In this article, a novel broadband end-fire circularly polarized antenna is presented. It comprises a diamond-shaped shorted parallel-plate cavity (DSPC) and planar symmetrical conductor arms (PSCA). The DSPC and PSCA serve as the electric and magnetic dipole, respectively. By adjusting the aperture of DSPC and bending angle of PSCA, the impedance bandwidth and the axial-ratio bandwidth are greatly improved. Meanwhile, the end-fire circles are employed to improve the gain of an antenna. The overall size of the antenna is 35.5 mm × 38.2 mm × 2 mm, equal to 0.98 λ0 × 1.05 λ0 × 0.055 λ0 . The measured results show that the realized impedance bandwidth for S11 ≤ –10 dB is 14.1% (7.63–8.79 GHz) and 3-dB AR bandwidth is 16.4% (7.57–8.92 GHz). A good agreement between the simulated and measured results is obtained.